Mobility and Recombination of Charge Carriers in Polymer and Mica Electrets - G.K. Novikov; A.I. Smirnov; V.V. Fedchishin (Учёные записки Казанского университета: Серия Физико-математические науки)
The mobility of electrons µe and holes µp was measured for the first time using the method of creating the radiation thickness gradient of recombination center concentration Np(h) in dielectrics exposed to ionizing radiation of the electric corona and electric barrier gas discharge.